2021
DOI: 10.1097/aog.0000000000004570
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Adverse Childhood Experiences and Adverse Pregnancy Outcomes

Abstract: OBJECTIVE: To examine the association between adverse childhood experiences and adverse pregnancy outcomes. METHODS: This cohort study included individuals who enrolled in a perinatal collaborative mental health care program (COMPASS [the Collaborative Care Model for Perinatal Depression Support Services]) between 2017 and 2021. Participants completed psychosocial self-assessments, including an adverse childhood experiences screen. The primary exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 38 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…ACEs and adverse pregnancy outcomes such as hypertensive disorders of pregnancy and pre-term birth 6,7 ; and ACEs and mental and substance use disorders, cardiovascular disease and early mortality. 8,9 Pregnancy is an optimal time to identify existing health risks in women and provide interventions that may prevent future health problems for women, children and their families.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACEs and adverse pregnancy outcomes such as hypertensive disorders of pregnancy and pre-term birth 6,7 ; and ACEs and mental and substance use disorders, cardiovascular disease and early mortality. 8,9 Pregnancy is an optimal time to identify existing health risks in women and provide interventions that may prevent future health problems for women, children and their families.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Australia, nearly two in three children are exposed to at least one ACE 2 . Since the landmark ACE study by Felitti and colleagues reporting a significant association between ACEs and poor physical and mental health outcomes throughout life, 3 research has expanded to additional populations providing consistent evidence of the associations between ACEs and pregnancy intentions 4,5 ; ACEs and adverse pregnancy outcomes such as hypertensive disorders of pregnancy and pre‐term birth 6,7 ; and ACEs and mental and substance use disorders, cardiovascular disease and early mortality 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple links between interpersonal violence and abortion care have been established (Basile et al, 2022; Miller et al, 2021), including pregnancy in the context of rape or incest and the association between early interpersonal trauma (e.g., childhood sexual abuse) and negative reproductive health outcomes including unwanted pregnancy. Research has also demonstrated that being denied a wanted abortion increases the likelihood of physical violence from the male-involved partner two and a half years after an unwanted pregnancy (Roberts et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous cross-sectional studies have estimated a substantial ACE-associated health economic burden in adulthood in Europe and North America, the UK, and California . To our knowledge, similar economic estimates do not yet exist for other US states or for the US in total, although the ACE-related health burden among adults is extensively documented . This study aimed to estimate the economic burden of health conditions associated with ACEs among US adults.…”
Section: Introductionmentioning
confidence: 95%